Telehealth and in-person HIV care during the COVID-19 pandemic at a large academic medical center in North Carolina - Valerie Yelverton; Jan Ostermann; Michael E. Yarrington; Andrew K Weinhold; Nabil Natafgi; Bankole Olatosi; Sharon Weissman; Nathan M Thielman (PLoS ONE, 2025)
Background To maintain HIV care during the COVID-19 pandemic, many HIV clinics across the United States adopted telehealth. However, not everyone participated in telehealth equally. This study assessed the use and disparities in telehealth and in-person HIV care at a large academic medical center in North Carolina (NC) relative to the COVID-19 pandemic. Methods Data from the Duke University Infectious Disease clinic in NC were extracted from electronic health records (EHR), aggregated across persons with HIV (PWH) by calendar month, visit type (in-person vs. telehealth HIV care), and by key sociodemographic and clinical characteristics. Variation in HIV care over time was analyzed graphically by age, sex, race and ethnicity, county of residence, and viral load (VL) history. Results EHR data from 2,623 PWH receiving care between January 2019 and March 2023 were included. Telehealth use sharply increased in the first months of the pandemic and decreased thereafter. Telehealth use was higher among non-Hispanic Whites compared to People of Color. Most PWH (93%) had a first post-onset-of-the-pandemic (pop) HIV care visit on March 16, 2020 and thereafter. The proportion of telehealth first pop visits peaked in April 2020 with 88% telehealth visits. Conclusions Telehealth bridged the initial COVID-19 pandemic phase with drastically reduced in-person visit availability, yet it was not equally utilized across race and ethnicity groups. To guide the optimal integration of telehealth in HIV care and promote equitable care in the future, HIV care outcomes need to be closely monitored, and strategies designed to promote access for Communities of Color are needed.